Prevalence of Edentulism in Diabetic and Non – Diabetic Patients in Central India - Jain, Ankush; Patel, Poonam; Sudhapalli, Swathi; Srivastava, Rajeev; Makker, Raveena; Khandelwal, Sourabh (Journal of Neonatal Surgery, 2025)
N